Community PMTCT Challenges: Operational Issues in Testing Pregnant Women Without ANC Through CBOs Versus the ANC and Testing Model in Congregation Settings - Apo-Oyin, Aramide; Dave-Agboola, Itunu Omolade; Okosa, Bridget; Musa Shallangwa, Joy; Niyang, Piringar Mercy; Gobir, Ibrahim Bola (British Journal of Healthcare and Medical Research, 2025)
This paper examines operational challenges in implementing two community-based Prevention of Mother-to-Child Transmission (PMTCT) of HIV approaches in Northern Nigeria: testing pregnant women without antenatal care (ANC) through community-based organizations (CBOs) and the ANC and Testing Model in congregation settings (Tabbatacciyar Kulawar Iyali). Based on implementation experiences from the Accelerating Control of HIV Epidemic in Nigeria - Cluster 2 (ACE 2) project, we analyze operational issues including access, training, data management, and comparative effectiveness. The congregation-based approach demonstrated higher yield in identifying HIV-positive pregnant women despite challenges (Gobir et al., 2025). We provide recommendations for strengthening both approaches to reach pregnant women who do not access conventional healthcare services.